2018
DOI: 10.1007/s11011-018-0307-2
|View full text |Cite
|
Sign up to set email alerts
|

L-3-n-Butylphthalide reduces ischemic stroke injury and increases M2 microglial polarization

Abstract: Overwhelming evidence suggests that microglia play an important role in ischemic injury and they polarize into two different phenotypes with distinct functions after ischemic stroke. We performed the present study to investigate whether L-3-n butylphthalide (NBP) has an effect on microglial polarization. Mice were subjected to transient middle cerebral artery occlusion (MCAO) for 45 min, and then immediately after reperfusion were treated with NBP or vehicle via the caudal vein for 7 consecutive days. 2,3,5-Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Some Chinese scholars (Wang, Ma, et al, ) have summarized the research progress of NBP in the treatment of ischemic stroke in the past 20 years, and it was considered as a promising drug for ischemic stroke. A large number of experiments at home and abroad have revealed that NBP can regulate brain energy metabolism (Yan, Wang, Yao, Liu, & Xiao, ), protect the mitochondria (Min et al, ), promote normal blood flow in the ischemic area (Xu et al, ), inhibit oxidative stress and platelet aggregation (Li et al, ; Zhao, Li, Zhang, Chen, & Li, ), and prevent the vigorous apoptosis of cells (Min et al, ). In addition, Chinese scholars found that NBP plays a neuroprotective role by acting on multiple active targets (Wang et al, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some Chinese scholars (Wang, Ma, et al, ) have summarized the research progress of NBP in the treatment of ischemic stroke in the past 20 years, and it was considered as a promising drug for ischemic stroke. A large number of experiments at home and abroad have revealed that NBP can regulate brain energy metabolism (Yan, Wang, Yao, Liu, & Xiao, ), protect the mitochondria (Min et al, ), promote normal blood flow in the ischemic area (Xu et al, ), inhibit oxidative stress and platelet aggregation (Li et al, ; Zhao, Li, Zhang, Chen, & Li, ), and prevent the vigorous apoptosis of cells (Min et al, ). In addition, Chinese scholars found that NBP plays a neuroprotective role by acting on multiple active targets (Wang et al, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…2). Various compounds in phytoextracts such as melatonin and L-3-nbutylphthalide from celery and polyphenols from cocoa have been shown to activate the M2 polarization of macrophages [22][23][24]. Flow-cytometry and qPCR analysis showed that the extracts signi cantly inhibited TNF-α and IL-1β by suppression of M1 polarization in the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of cerebral apoplexy, NBP was mainly used for inhibiting platelet aggregation, reducing thrombosis, improving microcirculation, reducing the volume of cerebral infarction, resisting oxidative stress, protecting mitochondrial function, reducing neuronal apoptosis, alleviating inflammatory reaction, mediating autophagy of nerve cells, promoting neurogenesis and targeting in several pathophysiological mechanisms, which are mainly reflected in its obvious neuroprotective effect. [16][17][18][19][20][21][22][23][24][25][26] After further studies on its application, it was found that the beneficial effects of NBP are beyond those of apoplexy. Especially in neurodegenerative disease fields, it was found that NBP and its ramifications have unique function and effects in AD, vascular dementia (VaD), PD, ALS and DEACMP treatment.…”
Section: Introductionmentioning
confidence: 99%